Gamma irradiation effects on ochratoxin A: Degradation, cytotoxicity and application in food. (1st February 2018) - Calado, Thalita; Fernández-Cruz, María Luisa; Cabo Verde, Sandra; Venâncio, Armando; Abrunhosa, Luís
Highlights: Ochratoxin A (OTA) was easily degraded by gamma radiation when dissolved in water. Dry OTA was extremely resistant to gamma radiation. In wheat flour, a radiation dose of 30.5 kGy eliminated 24% of the OTA. In grape juice, a radiation dose of 30.5 kGy eliminated 12% of the OTA. In wine, a radiation dose of 30.5 kGy eliminated 23% of the OTA. Abstract: Ochratoxin A (OTA) is one of the main mycotoxins that can be found in food. The use of gamma radiation is a technique for preserving food that may exert some effects on mycotoxins. OTA was irradiated in its dry form, in aqueous and in methanolic solutions, and in wheat flour, grape juice and wine. Additionally, the toxicity of OTA irradiated in water was tested. In aqueous solutions, more than 90% of the OTA was degraded by γ-radiation doses ≥2.5 kGy, and a 2-fold reduction in OTA cytotoxicity was observed. In food matrices, the elimination of OTA by γ-radiation was found more difficult, as radiation doses of 30 kGy eliminate at most 24% of the OTA. Higher moisture content of food matrices did not substantially increase OTA elimination. It is concluded that OTA is very sensitive to irradiation in water solutions but resistant in its dry form and in food matrices.